The Role of Artificial Intelligence in Tourism Marketing - Brief Overview of Serbian Situation - Muhi, Bela (Poslovna ekonomija, 2025)
In recent years, the dynamic development of information and communication technology had a huge impact on marketing. Today, we are witnessing a new revolutionary transformation: artificial intelligence (AI) is revolutionizing the world of business, education, healthcare, tourism, marketing, etc. AI is already an integral part of our present, and can be applied in many areas. New opportunities are also opening up in the world of tourism marketing. In this study, some of the most important opportunities for the use of AI in marketing and tourism marketing are presented, also the situation in Serbia is presented, i.e. where is the use of AI in the country in general and in the field of tourism marketing.